2019
DOI: 10.3390/jfb10030043
|View full text |Cite
|
Sign up to set email alerts
|

Striking Differences in Platelet Distribution between Advanced-Platelet-Rich Fibrin and Concentrated Growth Factors: Effects of Silica-Containing Plastic Tubes

Abstract: Compared with platelet-rich plasma, the preparation of platelet-rich fibrin (PRF) is simple and has not been overly modified. However, it was recently demonstrated that centrifugation conditions influence the composition of PRF and that silica microparticles from silica-coated plastic tubes can enter the PRF matrix. These factors may also modify platelet distribution. To examine these possibilities, we prepared PRF matrices using various types of blood-collection tubes (plain glass tubes and silica-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
(45 reference statements)
1
32
0
3
Order By: Relevance
“…Also, different concentrations of CGF among the donors, different blood volumes used for CGF preparation, and different periods used for preparing CGF extract could disturb the results. Another agent is the test tube used for blood collection, which its material may interfere with the properties of CGF (Bonazza et al, ; Tsujino et al, ). The release dynamics of growth factors should be considered before obtaining the extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, different concentrations of CGF among the donors, different blood volumes used for CGF preparation, and different periods used for preparing CGF extract could disturb the results. Another agent is the test tube used for blood collection, which its material may interfere with the properties of CGF (Bonazza et al, ; Tsujino et al, ). The release dynamics of growth factors should be considered before obtaining the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Another agent is the test tube used for blood collection, which its material may interfere with the properties of CGF (Bonazza et al, 2016;Tsujino et al, 2019 (Borsani et al, 2015), more sophistical research showed that some of the growth factors are released during 8 hr, while the release of some others continues throughout 13 days (Dohan Ehrenfest, de Peppo, Doglioli, & Sammartino, 2009;Honda et al, 2013;Zumstein et al, 2012). Based on these differences, the optimum concentration of CGF could vary in studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of CGF matrices (Kobayashi et al, 2012), we examined platelet distribution on the surface regions using SEM and obtained similar findings. While comparing glass tubes to silica-coated tubes (Tsujino et al, 2019b), we previously demonstrated that high-speed centrifugation accumulated platelets on the distal surface regions in glass-prepared matrices, but homogeneously in silica-prepared matrices.…”
Section: Difference In Platelet Distribution In Glassand Silica-prepamentioning
confidence: 95%
“…From the results of SEM and additionally of immunohistochemical staining or simulation studies using liquid PRF preparations (Kobayashi et al, 2012;Watanabe et al, 2017;Miron et al, 2019a;Tsujino et al, 2019b), it is generally believed that centrifugation distributes platelets based on the difference in density gradient in the PRF matrix and in the plasma fraction of citrated blood samples. Thus, platelet density decreases as the distance to the rotor axis decreases (Kobayashi et al, 2012;Ghanaati et al, 2014;Dohan Ehrenfest et al, 2018;El Bagdadi et al, 2019;Miron et al, 2019a).…”
Section: Difference In Platelet Distribution In Glassand Silica-prepamentioning
confidence: 99%
“…Some studies have demonstrated that PCs obtained by blood collected in glass or silica-coated tubes presented different buffy-coat morphology, fibrin architecture and platelet/leukocyte distribution in the PC matrix [42]. Furthermore, silica micro-particles may be released by tube walls during centrifugation procedures, entrapped in PC matrix, thus modifying platelet distribution in the end-product [43].…”
Section: Devicementioning
confidence: 99%